Synthesis and In Vitro Evaluation of Novel 1,2,3,4-Tetrahydroisoquinoline Derivatives as Potent Antiglioma Agents - Patil, Renukadevi; Hosni-Ahmed, Amira; S. Jones, Terreia; A. Patil, Shivaputra; B. Asres, Likeselam; Wang, Xiangdi; C. Yates, Ryan; E. Geisert, Eldon; D. Miller, Duane (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Glioblastoma Multiforme (GBM) continues to demand improved chemotherapeutic solutions. In order to discover novel chemotherapeutic agents for GBM, we identified novel tetrahydroisoquinoline (THI) analogs as antiglioma agents. The present study reports the design, synthesis and in vitro evaluation of new THI derivatives in four established human glioma cell lines (T98, U87, LN18 and A172). Our structure activity relationship (SAR) studies revealed that the important modification of the carbon linker between the biphenyl and THI ring yielded EDL-360 (12) as a potent antiglioma agent (LN18; IC50: 5.42 ±0.06 μM) and is considered to be our new lead drug candidate for further preclinical studies.
Keywords: EDL-155 analogs